Carbon‐Based Photothermal Actuators - Han, Bing; Zhang, Yong‐Lai; Chen, Qi‐Dai; Sun, Hong‐Bo (Advanced functional materials, 2018)
Actuators that can convert environmental stimuli into mechanical work are widely used in intelligent systems, robots, and micromechanics. To produce robust and sensitive actuators of different scales, efforts are devoted to developing effective actuating schemes and functional materials for actuator design. Carbon‐based nanomaterials have emerged as preferred candidates for different actuating systems because of their low cost, ease of processing, mechanical strength, and excellent physical/chemical properties. Especially, due to their excellent photothermal activity, which includes both optical absorption and thermal conductivities, carbon‐based materials have shown great potential for use in photothermal actuators. Herein, the recent advances in photothermal actuators based on various carbon allotropes, including graphite, carbon nanotubes, amorphous carbon, graphene and its derivatives, are reviewed. Different photothermal actuating schemes, including photothermal effect–induced expansion, desorption, phase change, surface tension gradient creation, and actuation under magnetic levitation, are summarized, and the light‐to‐heat and heat‐to‐work conversion mechanisms are discussed. Carbon‐based photothermal actuators that feature high light‐to‐work conversion efficiency, mechanical robustness, and noncontact manipulation hold great promise for future autonomous systems. This review highlights the recent advances in carbon‐based photothermal actuators. Physical properties and light‐to‐heat conversion mechanisms of various carbon‐based functional materials are summarized. Photothermal actuating schemes such as photothermal expansion, desorption, phase change, surface tension effect, and magnetic susceptibility are reviewed. The current challenges and future perspectives of this field are also discussed.